2023
DOI: 10.1002/slct.202203530
|View full text |Cite
|
Sign up to set email alerts
|

Review of electrochemical transition‐metal‐catalyzed C−H functionalization reactions

Abstract: The combination of organometallic C−H activation and electro‐catalysis has emerged as a potent synthetic technique for various molecular scaffolds since it avoids the use of harmful and expensive chemical oxidants in stoichiometric amounts. Moreover, the pre‐functionalization of substrates is not required and newer ways to perform metal‐catalyzed C−H activation reactions are possible. Here, we have discussed eletrochemically driven C−H acyloxylation, acetoxylation, oxygenation, acylation, amination, alkylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 128 publications
0
4
0
Order By: Relevance
“…Prediction of pharmacokinetic properties [36] A computer analysis was carried out to prepare the ADME characteristics of the synthesized compound. It has been validated that the topological polar surface area (TPSA), or surface containing polar atoms, correlates using passive molecule via membranes.…”
Section: Docking Analysismentioning
confidence: 99%
“…Prediction of pharmacokinetic properties [36] A computer analysis was carried out to prepare the ADME characteristics of the synthesized compound. It has been validated that the topological polar surface area (TPSA), or surface containing polar atoms, correlates using passive molecule via membranes.…”
Section: Docking Analysismentioning
confidence: 99%
“…The merging of electrochemistry with transition‐metal catalysis for C−H functionalization has made substantial progress in recent years for myriad transformations [47–50] . Key benefits include the avoidance of stoichiometric metal salt oxidants, instead using electricity as a “green oxidant” (Scheme 2), and access to milder reaction conditions which are more tolerant of sensitive substrates and coupling partners.…”
Section: Introductionmentioning
confidence: 99%
“…The merging of electrochemistry with transitionmetal catalysis for CÀ H functionalization has made substantial progress in recent years for myriad transformations. [47][48][49][50] Key benefits include the avoidance of stoichiometric metal salt oxidants, instead using electricity as a "green oxidant" (Scheme 2), and access to milder reaction conditions which are more tolerant of sensitive substrates and coupling partners. Previous work by Chang and co-workers has shown that post-transmetalation intermediates of cyclometalated Ir, Rh, and Ru complexes can be prepared and isolated from respective aryl-and methylboronic coupling partners at mild temperature, which will undergo oxidatively induced reductive elimination to form a CÀ C bond once subjected to chemical or electrochemical oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, organic electrochemistry has attracted increasing attention due to its economical and environmentally benign reaction conditions, which involve the use of electricity instead of adding sacrificial oxidants or reductants to achieve target transformation. Hitherto, the combination of electrochemistry and transition-metal catalysis has evolved into an appealing protocol in exploring oxidative C–H bond functionalization for achieving challenging transformations. The pivotal electro-oxidation processes are presumed to oxidize the organometallic precursors to a higher oxidation state, allowing a more readily bond-forming reductive elimination. Notably, a series of conversions regarding the electro-oxidation-driven Rh-catalyzed C–H functionalization have been successfully realized. …”
Section: Introductionmentioning
confidence: 99%